Age-related cognitive bias in in-hospital cardiac arrest. (May 2021) - Holmberg, Mathias J.; Granfeldt, Asger; Moskowitz, Ari; Andersen, Lars W.; ,
Abstract: Aims: Cognitive bias has been recognized as a potential source of medical error as it may affect clinical decision making. In this study, we explored how cognitive bias, specifically left-digit bias, may affect patient outcomes in in-hospital cardiac arrest. Methods: Using the Get With The Guidelines® – Resuscitation registry, we included adult patients with an in-hospital cardiac arrest from 2011 to 2019. The primary outcome was survival to hospital discharge. Secondary outcomes included return of spontaneous circulation, favorable neurological outcome, and duration of resuscitation. Using a regression discontinuity design, we explored whether there was a sudden change in survival at the age threshold of 80 years which would indicate left-digit bias. Additional analyses were performed at age thresholds of 60, 70, and 90 years. Results: A total of 26, 784 patients were included for the primary analysis. The overall survival was 22% in this cohort. There was no discontinuity of survival below and above the age of 80 years (risk difference, 0.47%; 95%CI, −1.61% to 2.56%). Similar results were estimated for the secondary outcomes and for the age thresholds of 60, 70, and 90 years. The results were consistent in sensitivity analyses. Conclusions: There was no indication that cognitive bias based on age affected outcomes in in-hospital cardiac arrest in these data.